Overlap of membranous nephropathy and IgA nephropathy in a patient with Kimura’s disease: a case report and literature review - Barbosa, Géssica Sabrine Braga; Neves, Precil Diego Miranda de Menezes; Mohrbacher, Sara; Abdo, André Néder Ramires; Cavalcante, Lívia Barreira; Menezes, Yara de; Sato, Victor Augusto Hamamoto; Oliveira, Érico de Souza; Pereira, Leonardo Victor Barbosa; Bales, Alessandra Martins; Frediani, Marcella Martins; Chocair, Pedro Renato; et al. (Frontiers in Immunology, 2024)
Introduction: Kimura's disease (KD) is a rare chronic inflammatory disorder characterized by subcutaneous lymphoid hyperplasia with peripheral eosinophilia. Kidney involvement is reported in 15-18% adult patients with KD, in many cases as nephrotic syndrome. We present a case of overlapping Membranous Nephropathy and IgA Nephropathy associated with KD.Case report: A 27-year-old man was admitted with a history of bilateral leg edema for the last two months and concomitant progressive increase of cervical mass and fever. Laboratory findings: peripheral leukocyte count, 10080/mm³; eosinophils, 3200/mm³ (31.7%); serum creatinine, 0.83mg/dL; eGFR: 140ml/min per 1.73m 2 . In the urinalysis, presence of hematuria and proteinuria; 24-hour proteinuria: 12.9g; serum albumin, 1.3g/dL; elevated IgE level (750kU/L). Serologies for hepatitis B, hepatitis C, HIV and VDRL were all negative.Complement C3 and C4 levels were normal. No monoclonal protein was detected in blood and urine. Parasite infestation was discarded. A biopsy of the cervical lymph node revealed eosinophilic lymphoid hyperplasia, suggesting KD. A kidney biopsy revealed findings consistent with overlapping of Membranous Nephropathy with IgA nephropathy. The patient was treated for KD with prednisone 1mg/kg/d with progressive dose tapering and posterior association of methotrexate 15mg/week. A renin-angiotensin system inhibitor was prescribed for nephrotic syndrome. The cervical mass regressed, and proteinuria achieved partial remission, with an increase in serum albumin level and normalization of eosinophils and IgE levels.Although uncommon, kidney involvement must be kept in mind in patients with Kimura's disease. Glomerular diseases are the most frequent form of kidney injury.